Aggregation-induced emission enhancement -active triarylamine-based polyamides containing fused ring groups towards electrochromic smart window and sensor for HCl and TNP. (January 2021) - Li, Dongxu; Yang, Yan; Yang, Caiyu; Zhang, Wei; Wang, Yan; Lin, Xiaoxue; Gao, Yanyu; Lv, Xinying; Niu, Haijun; Wang, Wen
Abstract: A series of new polyamides (PAs) were designed and synthesized based on two novel triarylamines (TAA) with fused ring groups via phenyl bridge through the Suzuki coupling reaction. These novel PAs have amorphous structure and excellent thermal stability, with a carbon residue rate of up to 70% at 800 °C in nitrogen atmosphere. In the process of electrochemical oxidation, there is no obvious recessionary in current and transmittance over 1000s with a cycle time of 10s, which showing high contrast and excellent cycle stability. And the electrofluorochromic (EFC) performance can also be adjusted by being applied voltage. 1NAT-CA and 9AAT-CA have solvatochromic effect in absorption, fluorescence (PL) in solvents, 1NAT-6F and 1NAT-BA have aggregation-induced emission enhancement (AIEE) properties in solid state. The kind of multifunctional integrated PAs show characteristics of responding to voltage, explosive and hazardous gas stimuli and the stimuli-responsive mechanisms are investigated, which have the prospect of application in photoelectric sensors, explosive detectors and high-contrast displays. Graphical abstract: Image 1 Highlights: Triphenylamine-based polyamides (PAs) containing fused ring groups were prepared. PAs exhibite excellent electrochemical cycling stability and adjustable electroluminescent properties. PAs have theAIEE effect, solvatochromic effect and can be used as sensors for TNP and HCl.